Ethical Landscape Of Islamic Principles And Contemporary Challenges: A Comprehensive Exploration - Nasir Hassan Wani; Areesha Azhar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper provides a thorough examination of how Islamic ethics guide Muslims in navigating the complexities of contemporary challenges. Drawing from the Qur'an and the life of Prophet Muhammad, Islamic ethics offer a comprehensive framework that informs moral conduct in personal, social, economic, and environmental spheres. By carefully analyzing these teachings alongside the tradition of Ijtihad, Muslims approach modern ethical dilemmas with wisdom and compassion. Central values such as justice, compassion, honesty, and humility serve as guiding principles, shaping individual and collective behavior. The paper illustrates how Muslims engage with pressing issues like digital ethics, bioethics, environmental conservation, and global justice, seeking to harmonize religious teachings with contemporary realities. They grapple with privacy concerns, ethical technology use, genetic engineering, and end-of-life care while emphasizing stewardship of the environment and advocating for social justice. Through a steadfast commitment to ethical principles and a dedication to advancing justice and compassion, Muslims endeavor to fulfill their moral responsibilities and embody the ethical vision of Islam in today's world, contributing to a more equitable, compassionate, and sustainable global community.